Answer:
x = 3 and y = 2 or (3,2) in coordinate form
Explanation:
Given:
![\displaystyle \large{\begin{cases} x-y=1 \\ x+3y=9 \end{cases}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7p71qe6h7wjxxrzmas08ah6n6urpogmcik.png)
Solve by elimination of x-terms by multiplying either one of equations with -1:
For this, I choose to multiply -1 in first equation:
![\displaystyle \large{\begin{cases} -1(x-y=1) \\ x+3y=9 \end{cases}}\\\displaystyle \large{\begin{cases} -x+y=-1 \\ x+3y=9 \end{cases}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wiqot5d8mt3vwjnnfaa9d6xkg2o62zofs2.png)
Then add both equations:
![\displaystyle \large{-x+x+y+3y=-1+9}\\\displaystyle \large{4y=8}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o62mpi1dhplrz89q39lela9m761lf529cw.png)
Divide both sides:
![\displaystyle \large{(4y)/(4) = (8)/(4)}\\\displaystyle \large{y=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3rl3uo07dfpz5ve5lt2m538l6pdarr7ht3.png)
Next, substitute y = 2 in one of equations to solve for x:
For this, I choose to substitute y = 2 in the first equation:
![\displaystyle \large{x-y=1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sekdp7q188aawzsojgjmvn9a6dtia2m2ob.png)
Substitute y = 2 in:
![\displaystyle \large{x-2=1}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ytcn5fsxumsf46vz68kjznbhyfk7h3xu8y.png)
Add both sides by 2:
![\displaystyle \large{x-2+2=1+2}\\\displaystyle \large{x=3}](https://img.qammunity.org/2023/formulas/mathematics/high-school/vi5yszmq1l4b9mzcufbjdmppk32eqaoe9r.png)
Hence, the solution is x = 3 and y = 2 or you can write as in coordinate form (3,2)
__________________________________________________________
First method is elimination method, I’ll demonstrate another method which is by using matrices to find the solutions.
Given:
![\displaystyle \large{\begin{cases} x-y=1 \\ x+3y=9 \end{cases}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7p71qe6h7wjxxrzmas08ah6n6urpogmcik.png)
Write the system of equations in matrices form:
![\displaystyle \large{\left[\begin{array}{ccc}1&-1\\1&3\end{array}\right] \left[\begin{array}{ccc}x\\y\end{array}\right] =\left[\begin{array}{ccc}1\\9\end{array}\right]}](https://img.qammunity.org/2023/formulas/mathematics/high-school/v2l4s86g7a6le5lpyfghe7ai2ksu39xtag.png)
Let:
![\displaystyle \large{A=\left[\begin{array}{ccc}1&-1\\1&3\end{array}\right] }\\\displaystyle \large{X=\left[\begin{array}{ccc}x\\y\end{array}\right] \\\displaystyle \large{B = \left[\begin{array}{ccc}1\\9\end{array}\right] }](https://img.qammunity.org/2023/formulas/mathematics/high-school/pqsi71fi71tdnebtozu0397dzadgtes4xs.png)
From
where:
![\displaystyle \large{A^(-1)=(1)/(\det A) \left[\begin{array}{ccc}d&-b\\-c&a\end{array}\right] = (1)/(ad-bc) \left[\begin{array}{ccc}d&-b\\-c&a\end{array}\right] }](https://img.qammunity.org/2023/formulas/mathematics/high-school/h9o8vxv3ihoj7mohb9g4efhzsa55jce78t.png)
Find
:
![\displaystyle \large{\det A = ad-bc = 3+1=4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7e3v8axsttdt9g1nfu40dnqejlb2pia9h8.png)
Therefore:
![\displaystyle \large{A^(-1) = (1)/(4)\left[\begin{array}{ccc}3&1\\-1&1\end{array}\right]}\\\therefore \displaystyle \large{X = (1)/(4)\left[\begin{array}{ccc}3&1\\-1&1\end{array}\right] \left[\begin{array}{ccc}1\\9\end{array}\right]}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ovtdxfuiai8kgqdkcq30dn5bgrev05384d.png)
Evaluate the matrices:
![\displaystyle \large{X= (1)/(4)\left[\begin{array}{ccc}3(1)+1(9)\\-1(1)+1(9)\end{array}\right] }\\\displaystyle \large{X= (1)/(4)\left[\begin{array}{ccc}3+9\\-1+9\end{array}\right] }\\\displaystyle \large{X= (1)/(4)\left[\begin{array}{ccc}12\\8\end{array}\right]}\\\displaystyle \large{X= \left[\begin{array}{ccc}3\\2\end{array}\right] }\\\therefore \displaystyle \large{\left[\begin{array}{ccc}x\\y\end{array}\right] = \left[\begin{array}{ccc}3\\2\end{array}\right]}](https://img.qammunity.org/2023/formulas/mathematics/high-school/d4cyp4jd3fiicwrviapdeo5vxka30dxqh4.png)
Therefore, the solution is x = 3 and y = 2